Analisis Penerimaan Pajak Restoran terhadap Pendapatan Asli Daerah dan Produk Domestik Regional Bruto di Kota Banjarmasin - Izati, Fitria; Saipudin, Saipudin (PPJP Universitas Lambung Mangkurat, 2023)
This study aims to determine the effectiveness of the restaurant tax, the contribution of the restaurant tax to local revenue, and the elasticity of the restaurant tax on GRDP in Banjarmasin from 2011 to 2020. This research makes use of descriptive and quantitative research methods. The data is secondary from the Central Statistics Agency and BPKPAD. The results showed that the extent of the effectiveness of restaurant tax revenues was categorized as very effective, with a mean of 112.85%. In the meantime, the contribution of restaurant tax to local revenue remains less significant, with a standard of 14.27%. The elasticity of restaurant tax revenue on GRDP has a standard of -79.25%, which is classified as inelastic, meaning that every 1% change in GRDP can lessen the realization of restaurant taxes using -79.25.